Estimativa de desempenho de uma NoC a partir de seu modelo em SYSTEMC-TLM. - Sepúlveda Flórez, Martha Johanna (2006)
The wide variety of interconnection structures presently nowadays for SoC (Systemon- Chip), bus and networks-on-Chip NoCs, each of them with a wide set of setup parameters, provides a huge amount of design alternatives. Although the interconnection structure is a key SoC component, there are few design tools in order to set the appropriate configuration parameters for a given application. An efficient SoC project may comply an exploration stage among the possible solutions for the communication structure, during the first steps of the design process. The absence of appropriate tools for that exploration makes critical the designer?s judgment. The present study aims to enhance the communication SoC structure design area, when a NoC is used. This work proposes a methodology that allows the establishment of the NoC communication parameters using a high level model (SystemC TLM timed). Our approach analyzes and evaluates the NoC performance under a wide variety of traffic conditions. The experimental stage was conducted employing a model of a net represented by a SystemC TLM timed (Hermes_Temp). Parametric and pseudo-random generators control the network traffic. The analysis was carried on with a tool designed for these purpose, which generates a group of performance metrics. The results allow to elucidate the global and inner network behavior. The performance values are useful for the heterogeneous and homogeneous NoC design projects, improving the performance evaluation studies scope.